Arbovirus-Mosquito Vector-Host Interactions and the Impact on Transmission and Disease Pathogenesis of Arboviruses - Huang, Yan-Jang S.; Higgs, Stephen; Vanlandingham, Dana L. (Frontiers in Microbiology, 2019)
Hundreds of viruses, designated as arboviruses, are transmitted by arthropod vectors in complex transmission cycles between the virus, vertebrate host, and the vector. With millions of human and animal infections per year, it is critical to improve our understanding of the interactions between the biological and environmental factors that play a critical role in pathogenesis, disease outcomes, and transmission of arboviruses. This review focuses on mosquito-borne arboviruses and discusses current knowledge of the factors and underlying mechanisms that influence infection and transmission of arboviruses and discusses critical factors and pathways that can potentially become targets for intervention and therapeutics.